Chemosensory-Driven Foraging and Nocturnal Activity in the Freshwater Snail Rivomarginella morrisoni (Gastropoda, Marginellidae): A Laboratory-Based Study - Navapong Subpayakom; Pongrat Dumrongrojwattana; Supattra Poeaim (Journal of Zoological and Botanical Gardens, 2025)
Rivomarginella morrisoni is a freshwater snail endemic to Thailand, yet its behavioral ecology remains poorly understood. This study described the feeding behavior of R. morrisoni, focusing on its foraging activity, behavioral patterns, and food detection mechanisms under laboratory conditions using specimens collected from four river basins in central Thailand. Daily monitoring revealed nocturnal emergence, peaking between 21:00 and 22:00 h, with stable rhythms established 72 h post-feeding. Feeding trials revealed a preference for aged shrimp over fresh or decayed ones. Behavioral observations confirmed that food localization in R. morrisoni was mediated by chemical cues. Light–dark tests indicated a slight tendency toward darkness, but no significant phototactic response was observed. These findings suggest that R. morrisoni is a generalist scavenger with chemosensory-driven foraging and nocturnal activity. Its apparent sensitivity to habitat disturbance underscores the relevance of behavioral studies for informing future conservation and captive breeding efforts.
Keywords: Aquatic Invertebrate Ecology and Behavior; Mollusks and Parasites Studies; Freshwater macroinvertebrate diversity and ecology